Nail-holding Power of a few Mysore Woods on a Mohr and Federhaff Universal Testing Machine - Chelyaraja, B. K. (Indian Forester, 1957)
(i)The Universal Testing Machine of Mohr and Federhaff can be adapted to test the nail-holding power of woods. (ii) In general, greater the specific gravity better is the nail-holding power of woods, exceptions to this being due to other characteristics of the species concerned. (iii) The nail-holding power of woods has shown improvement if nails are driven to greater depth. (iv) Nailing in the side grain should be preferred to nailing in the end grain. (v) It is difficult to nail hard dense woods and they have a tendency to split while nailing. As opposed to this, the less dense woods can be nailed easily and they have less tendency to split while nailing, and hence are capable of taking more nails.